Argument-driven inquiry learning model to improve students' argumentation skills in science learning: systematic literature review - Melta, Defrian; Azhar, Minda; Yohandri, Yohandri; Arsih, Fitri; Razak, Abdul (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This research aims to identify and describe the Argument-Driven Inquiry (ADI) learning model to improve students' argumentation skills in science learning. The method used in this research is the Systematic Literature Review (SLR) method. From the search strategy results, 75 articles were found from 2017 to 2023, then selected gradually and systematically into 20 articles relevant to the topic of the ADI model in science learning. The analysis of journal article reviews based on SLR proves that the ADI learning model can be implemented using various learning media and significantly influences students' argumentation abilities in science learning. Apart from that, this argumentation ability also provides improvement for students who have different academic abilities. The ADI model can also improve other skills, such as understanding concepts, critical thinking, and learning outcomes.